Assessment of job satisfaction, work-related strain, and perceived stress in nurses working in different departments in the same hospital: A survey study - Erdoğan, Cem; Doğan, Sibel; Çakmak, Rümeysa; Kızılaslan, Deniz; Hızarcı, Burcu; Karaaslan, Pelin; Öz, Hüseyin (Springer, 2020)
ObjectiveWe aimed to evaluate whether working at ICU, inpatient services, or the operating room creates differences in job satisfaction (JS), work-related strain (WRS), and perceived stress (PS) of nurses.Research methodologyThe study data were collected through face-to-face interviews. The data collection tools utilized in the study included a questionnaire form consisting of 19 questions.Work-Related Strain Inventory (WRSI), Short-Form Minnesota Job Satisfaction Questionnaire (SF-MSQ), and the Perceived Stress Scale (PSS) were used.ResultsAcross all groups, the mean scores of SF-MSQ were statistically significantly the lowest in the groups of nurses, who were not economically satisfied with their salaries at all, who reported that they did not do their dream jobs and that they were not fond of their jobs.The mean scores of WRSI were statistically significantly the lowest across all groups in the groups of nurses.The mean PSS scores were statistically significantly the lowest across all compared groups in the groups of nurses, who commute to work by their private cars.ConclusionHospital management and nursing services should address the overtime working conditions of nurses and provide satisfactory wage improvements.
Keywords: Hospital; Job Satisfaction; Work-Related Strain; Perceived Stress; Nurse